Improvement of forage quality by means of molecular breeding in tropical grasses - Gondo, Takahiro (2010)
Many important warm- season perennial grasses multiply either by vegetative propagation, or form their seeds by an asexual mode of reproduction called apomixes. Possibility of improving of these plants by conventional breeding method depends on availability of natural genetic variation and its manipulation through breeding and selection. However, there are naturally not many genetic variations in apomictic grasses to generate new genetic variation. Plant tissue culture techniques have complemented conventional plant breeding programs. The author established a system for plant regeneration from in vitro-cultured calluses, suspension cells and protoplasts in some tropical grass species including apomictic species. In addition, we focus on describing current and future applications and impact of genetic transformation in tropical grasses.